A4 7 Okay, but what’s the Speed of Dark? - Savic, Natasha; Birch, Hannah; Tzabach, Lee (Physics Special Topics, 2023)
In this paper, we investigate how long Count Dracula, from the show ‘Young Dracula’, would have to travel at half the speed of light, 0.5c, for him to reach 600 years old, his age on the show, relative to a stationary observer on Earth. Using the equation for time dilation, we find that he would need to travel for 520 years. Using the kinetic energy equation, we also find that he would require 6.04 × 10^9 J of energy to travel at this velocity.